Long‐Term Crop Rotation Effects on Production, Grain Quality, Profitability, and Risk in the Northern Great Plains. (1st May 2017) - Smith, Elwin G.; Zentner, Robert P.; Campbell, Con A.; Lemke, Reynald; Brandt, Kelsey
Abstract : Core Ideas: Diversified rotations are more productive and profitable than cereal only rotations. Fallow rotations are less profitable than continuous cropping in the Northern Plains. Continuous cropping is riskier; however, it is preferred when averse to risk. Crop production in the semiarid Northern Great Plains has historically been limited to wheat ( Triticum aestivum L.), with fallow every second or third year. In response to current prices and new production technologies, these cropping systems have been replaced with reduced frequency of fallowing and inclusion of oilseed and pulse crops in the rotation. This study examined the long‐term changes that producers can expect in their production levels and economic returns for five wheat‐based rotations with different fallow frequencies, use of an annual legume green manure to partially replace fallow, and a continuous diversified rotation of cereal–oilseed–cereal–pulse crops. The findings were based on the last 11 yr of a 28‐yr (1987–2014) crop rotation experiment performed at Swift Current, SK, Canada. Despite the higher grain yield on fallow versus stubble, total grain production increased as fallow frequency decreased. The continuous wheat rotation produced 21% more wheat than the rotations with fallow. Wheat protein was highest for the rotation containing the legume green manure. Since its establishment in 2003, a wheat–canola ( Brassica napus L.)–wheat–dry pea ( Pisum sativum L.) rotation was more profitable than the traditional wheat systems. Participation in a crop insurance program reduced the financial risk from low crop yields, particularly for continuous cropping. We concluded that under current economic conditions and production practices, producers can indeed enhance production levels and farm profitability with adoption of more intensive (reduced fallow) crop rotations, particularly those that also include oilseed and pulse crops.